2018
DOI: 10.29252/qums.12.5.53
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alternative Healthy Eating Index (AHEI-2010) with Obesity Status, Serum Level of 25-Hydroxyvitamin D, hs-CRP in the Elderly of Tehran City, (Iran)

Abstract: Background and Objectives: Obesity is a worrying problem in the present age and is the cause of many chronic non-communicable diseases. Several nutritional and non-nutritional factors are involved in the emergence of this health crisis. One of the important nutritional factors is the quality of nutrition. In this study, the relationship of the Alternative Healthy Eating Index (AHEI-2010) in relation to obesity, vitamin D3, and CRP, was investigated in the elderly. Methods: This descriptive-analytic (cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In the present research, there was an inverse association between the HEI-2015 total score and the odds of having MetS. Similarly, in a previous study, an inverse association between MetS and HEI was reported in 226 elderly [ 30 ]. In another study conducted on 4,450 American adolescents, MetS prevalence decreased by increasing the score of HEI [ 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the present research, there was an inverse association between the HEI-2015 total score and the odds of having MetS. Similarly, in a previous study, an inverse association between MetS and HEI was reported in 226 elderly [ 30 ]. In another study conducted on 4,450 American adolescents, MetS prevalence decreased by increasing the score of HEI [ 31 ].…”
Section: Discussionsupporting
confidence: 86%